1988
DOI: 10.1093/bja/61.6.773
|View full text |Cite
|
Sign up to set email alerts
|

Ilioinguinal Nerve Blockade for Analgesia After Caesarean Section

Abstract: Bilateral ilioinguinal nerve blockade was performed, using 0.5% plain bupivacaine 10 ml to each side, in 13 patients having elective Caesarean section under general anaesthesia. Pain scores and requirement for postoperative analgesia were compared with 13 patients in a control group. Pain scores were less in the block patients at all times during the first day after operation, with the exception of 12 h. There was an increased time from the patient's recovery from anaesthesia to the first injection of opioid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 4 publications
4
10
0
Order By: Relevance
“…Moreover, our finding was also consistent with a study conducted by Bunting et al Bell et al and Ganta et al, where the mean VAS score was low in those who received II-IH block compared with the placebo group in parturients underwent caesarean delivery [12,22]. In addition, in another study, VAS pain scores were decreased both at rest and upon coughing in block group compared to the placebo group [3].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, our finding was also consistent with a study conducted by Bunting et al Bell et al and Ganta et al, where the mean VAS score was low in those who received II-IH block compared with the placebo group in parturients underwent caesarean delivery [12,22]. In addition, in another study, VAS pain scores were decreased both at rest and upon coughing in block group compared to the placebo group [3].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study revealed a good analgesic effect of II-IH nerve block for parturients undergoing cesarean delivery under spinal [3,19,20] or general anaesthesia [2,12,21]. In our study, the pain was assessed using numeric rating scale and additional tramadol on request was given when the NRS ≥ 4.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…n ilioinguinal nerve block (IINB) is a simple and useful regional anesthesia technique for intraoperative and postoperative analgesia for inguinal surgery. [1][2][3] This technique has proved to be superior and cost-effective in comparison with both subarachnoid and general anesthesia. 4 A carefully performed blockade may also be helpful in the differential diagnosis of chronic inguinal and lower abdominal pain.…”
mentioning
confidence: 99%